THE TEACHINGS OF CATUR MARGA: Critical Reflection on Constructivism Learning and its Relevance to UNESCO's Four Pillars of Education - I Ketut Wisarja; Ni Nyoman Suastini; Ni Wayan Aryani (IAHN-TP Palangka Raya, 2024)
The general assumption that education is a means of acquiring knowledge is indisputable, but the opinion that education is only obtained in a formalist environment is very naive, because it excludes other possibilities where education is also obtained from non-formal education models (andragogical), such as; pasraman education, ashram education, pesantren education, etc. The conservative paradigm with all its attributes, such as; educational fundalism, educational intellectualism, and educational conservatism, is basically more towards achieving a quo-vadis form of education and maintaining harmonization. The conservative paradigm with all its attributes, such as; educational fundalism, educational intellectualism, and educational conservatism, is basically more towards achieving a quo-vadis form of education and maintaining harmony only, without any criticism of all pre-conditions and post-conditions of existing knowledge and awareness. This concept is basically not too far from a mere